2020
DOI: 10.1213/ane.0000000000005075
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Plane Block With Liposomal Bupivacaine for Pain After Cesarean Delivery in a Multicenter, Randomized, Double-Blind, Controlled Trial

Abstract: BACKGROUND: In women undergoing cesarean delivery under spinal anesthesia with intrathecal morphine, transversus abdominis plane (TAP) block with bupivacaine hydrochloride (HCl) may not improve postsurgical analgesia. This lack of benefit could be related to the short duration of action of bupivacaine HCl. A retrospective study reported that TAP block with long-acting liposomal bupivacaine (LB) reduced opioid consumption and improved analgesia following cesarean delivery. Therefore, we performed a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 22 publications
0
66
0
2
Order By: Relevance
“…Our results indicated statistically significant reduction of pain with the use of LB for TAP block at 12 h (MD: −0.89, 95% CI: −1.44, −0.34 I 2 = 0% p = 0.01), 24 h (MD: −0.64, 95% CI: −1.21, −0.06 I 2 = 0% p = 0.03), 48 h (MD: −0.40, 95% CI: −0.77, −0.04 I 2 = 0% p = 0.03) but not at 72 h (MD: −0.37, 95% CI: −1.31, 0.56 I 2 = 57% p = 0.43) ( Figure 2). Nedeljkovic et al (30) in their study reported a statistically significant difference in pain scores between LB and RB at all time intervals up to 72 h. Hutchins et al (34) reported significantly lower maximal pain scores in the LB group at 24-, 48-, and 72-h time points compared to the RB group.…”
Section: Primary Outcomesmentioning
confidence: 87%
See 4 more Smart Citations
“…Our results indicated statistically significant reduction of pain with the use of LB for TAP block at 12 h (MD: −0.89, 95% CI: −1.44, −0.34 I 2 = 0% p = 0.01), 24 h (MD: −0.64, 95% CI: −1.21, −0.06 I 2 = 0% p = 0.03), 48 h (MD: −0.40, 95% CI: −0.77, −0.04 I 2 = 0% p = 0.03) but not at 72 h (MD: −0.37, 95% CI: −1.31, 0.56 I 2 = 57% p = 0.43) ( Figure 2). Nedeljkovic et al (30) in their study reported a statistically significant difference in pain scores between LB and RB at all time intervals up to 72 h. Hutchins et al (34) reported significantly lower maximal pain scores in the LB group at 24-, 48-, and 72-h time points compared to the RB group.…”
Section: Primary Outcomesmentioning
confidence: 87%
“…For the first primary outcome of our study i.e., total analgesic consumption, a meta-analysis could not be performed owing to significant differences in data collection and presentation among the included studies. Examining the results by specific periods, out of three studies (30,31,36) evaluating analgesic consumption for 0-48 h, only Nedeljkovic et al (30) reported statistically significant results. Hutchins et al (33,34) in their two trials reported analgesic consumption for 24-48 and 48-72 h but with opposite results.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations